Body mass index, height and risk of lymphoid neoplasms in a large United States cohort. Issue 6 (1st June 2013) - Patel, Alpa V.; Diver, W. Ryan; Teras, Lauren R.; Birmann, Brenda M.; Gapstur, Susan M.
Abstract: Results from epidemiologic studies examining associations between body size and risk of non-Hodgkin lymphoma (NHL) are inconsistent, and etiology may vary by histologic subtype of disease. Using Cox proportional hazards regression, multivariable relative risks (RRs) and 95% confidence intervals (CIs) were computed for associations of body mass index (BMI) and height with NHL in the prospective American Cancer Society Cancer Prevention Study-II Nutrition Cohort. From 1992 to 2007, 2074 incident cases of NHL were identified among 152 423 men and women. Obese individuals (BMI ≥ 30 kg/m 2 ) had 23% higher incidence of NHL (95% CI 1.08–1.40) compared to those with normal weight (BMI 18.5–< 25 kg/m 2 ). Height was positively associated with NHL (RR = 1.25, 95% CI 1.10–1.43, sex-specific quintile 5 vs. 1). BMI associations were strongest for diffuse large B-cell lymphoma. Height was most strongly associated with chronic lymphocytic leukemia/small lymphocytic lymphoma and to a lesser extent with multiple myeloma. These findings provide further evidence that body size may play a role in the etiology of NHL, which is of public health importance given the rapid rise in obesity worldwide.